Cord Blood Serum (CBS)-Based Eye Drops Modulate Light-Induced Neurodegeneration in Albino Rat Retinas - Stefano Di Marco; Serena Riccitelli; Mattia Di Paolo; Emilio Campos; Marina Buzzi; Silvia Bisti; Piera Versura (Biomolecules, 2020)
Age-related macular degeneration (AMD) is one of the leading causes of visual loss in western countries, it has no cure, and its incidence will grow in the future, for the overall population aging. Albino rats with retinal degeneration induced by exposure to high-intensity light (light-damage, LD) have been extensively used as a model of AMD to test neuroprotective agents. Among them, trophic factors (NGF and BDNF) have been shown to play a significant role in photoreceptors’ survival. Interestingly, cord blood serum (CBS) is an extract full of chemokines and trophic factors; we, therefore, hypothesized that CBS could be an excellent candidate for neuroprotection. Here, we investigate whether CBS-based eye drops might mitigate the effects of light-induced retinal degeneration in albino rats. CBS treatment significantly preserved flash-electroretinogram (f-ERG) response after LD and reduced the “hot-spot” extension. Besides, CBS-treated animals better preserved the morphology of the outer nuclear layer, together with a reduction in microglia migration and activation. Interestingly, the treatment did not modulate reactive gliosis and activation of the self-protective mechanism (FGF2). In conclusion, our results suggest that CBS-based eye drops might be successfully used to mitigate retinal neurodegenerative processes such as AMD.